Long-term fire effects on soil and vegetation nitrogen cycling: potential links to persistent stream nitrate export - Rhea, Allison E., author; Covino, Timothy P. author; Rhoades, Charles C., author; CSIRO Publishing, publisher (Colorado State University. Libraries, 2026)
Background. Soil and stream nitrate concentrations often increase after severe fire from elevated nitrogen (N) mineralization and reduced plant uptake. However, it is unclear how long these effects persist and contribute to stream N export. Aims. We examined the contribution of soil N supply and vegetation N demand to 19-fold higher stream export that has persisted since the 2002 Hayman Fire in Colorado, USA. Methods. We compared soil N pools, inorganic N production, subsurface (0-100 cm) concentrations, vegetation cover, productivity and N demand 17 years post-fire. We sampled along burned and unburned hillslopes to evaluate whether near-stream vegetation and soils attenuated N loss during downslope transport. Key results. Mineral soil, leachate and groundwater concentrations were higher in burned than unburned hillslopes, despite similar mineralization rates. Burned uplands showed 62% lower productivity and 28% lower N demand relative to unburned forests. Riparian recovery exceeded uplands but remained incomplete relative to unburned conditions. Burned uplands acted as N sources, with slight reductions in soil in downslope riparian soils. Conclusions. Sustained export was driven by reduced vegetation N demand and subsurface transport, not increased mineralization. Implications. Revegetation of severely burned uplands and riparian zones may enhance long-term N retention.
Keywords: hillslope; hydrologic connectivity; nitrogen cycling; revegetation; riparian; topography; upland; wildfire